An attempt to optimise the number of pupils in comprehensive secondary schools based on their learning outcomes - Jan Polcyn (Institute of Economic Research (IER), 2017)
There may be a significant correlation between the number of pupils in a school and their learning performance. Some studies point to the negative impact of schools with a large number of pupils on the educational results achieved. At the same time, the demographic crisis that has been deepening steadily for several years now represents an important motivation forrationalising the existing network of schools. The aim of the study was to determine the optimum size of schools based on the criterion of examination results expressed through educational value added. The analysis covered all comprehensive secondary schools in Poland over the2013 to 2015 period (a total of 1,943 schools). It determined the correlation between the size of a school expressed through the average number of graduates, and the results of thematura examination (the secondary schoolleaving exam in Poland) expressed through educational value added. Data for the analysis was obtained from the Section of Educational Value Added of the Educational Research Institute in Warsaw. The comprehensive secondary schools under study were divided into 5 classes, according to the criterion of the average annual number of graduates. The following analytical classes were distinguished: class A - up to 50 graduates, class B - 51-100 graduates, class C - 101-150 graduates, class D - 151 -200 graduates, class E - above 201 graduates. The analyses conducted in this study showed that the comprehensive secondary schools with over 600 pupils had the highest learning outcomes as expressed through educational value added. The lowest educational effectiveness was found in schools with less than 150 pupils. A dependency was discovered whereby the effectiveness of education increases as the number of pupils grows. Due to the lack of data concerning examination results in schools with more than 1,000 pupils (value indicated in American studies as the threshold value for positive learning outcomes), it was not possible to determine the maximum number of pupils that guarantees satisfactory learning outcomes.
Keywords: A20; A21; A29; 330; number of pupils in a school; educational value added (EVA); comprehensive secondary school; socio-cultural capital